English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Thank you for all that help!..
Im just unsure of this new stuff we're learning in class.
Thanks!

2006-11-16 12:33:14 · 5 answers · asked by Anonymous in Science & Mathematics Mathematics

Shoot, i typed the 9 ^ up there wrong. its supposed to be the (***

2006-11-16 12:37:59 · update #1

5 answers

Assuming your 9 was a typo, intended to be a parenthesis (they are the same key and I'm constantly mistyping 9...)

(a^3b^3)(ab)^-2

Then this is the same as:
(a^3b^3)/(a²b²).

You would cancel a²b² leaving only a and b in the numerator.

Thus your answer of 'ab' is exactly right! Good job!

2006-11-16 12:38:44 · answer #1 · answered by Puzzling 7 · 0 0

(9ab(a ^ 3 * b^ 3)) ^ -2
Think of a ^ 3 * b ^ 3 as one unit then evaluate 9ab(a ^ 3 * b^3)
9ab (a^3 * b^3) = 9 (a ^ 4 * b ^ 4) take that answer and raise it to the - 2 power. A formula for this is : z ^ -x = 1 / (z^x). Therefore,
9(a ^ 4 * b ^ 4) ^ -2 = 1 / (9(a^4 b^4)) ^ 2 = 1 / (81 (a ^ (4* 2) b ^ (4* 2))) = 1 / (81 (a^8 b^8))
To check, let a = 2 and b = 3.
9(2)(3) ((2 ^ 3) * (3^3)) ^ -2 = (54 * (8 * 27)) ^ -2 = 1 / (11664 ^ 2) = 1 / 136048896
Now check my answer with the same numbers
1 / 81 (2 ^ 8) (3 ^ 8) == 1 / (81 *256 * 1679616) = 1 / 136048896. It checks.

2006-11-16 21:14:44 · answer #2 · answered by j 4 · 0 0

well the parenthesis don match..
assumin it to be((a^3 b^3)9ab)^-2

it simplifies to 1/(3(ab)^2)

2006-11-16 20:41:46 · answer #3 · answered by Rajkiran 3 · 0 0

Um, no way. Did you copy this down correctly?

* * * * *

Right, like the next poster says... good detective work on his part.

2006-11-16 20:36:10 · answer #4 · answered by Anonymous · 0 0

(a^3b^3)(ab)^-2
= (a^3b^3)(a^-2)(b^-2)
= a^(3-2)b^(3-2)
=a^1b^1
=ab

2006-11-17 03:03:14 · answer #5 · answered by grandpa 4 · 0 0

fedest.com, questions and answers